The Slow Decay of Southern Africa's Dominant-Party Regimes - GIGA German Institute of Global and Area Studies - Leibniz-Institut für Globale und Regionale Studien, Institut für Afrika-Studien (2017)
Abstract: The successful national liberation movements of southern Africa have become dominant-party regimes. However, many now face a series of political and economic crises that have the potential to put the region's stability at risk. Dominant-party regimes in southern Africa base their legitimacy on liberating the nation from colonialism and being an expression of the people's will. However, they preside over an exclusionary social order. The promotion of formal measures of democratisation which focus on periodic elections, formal constitutions, and the existence of opposition parties have had limited success in loosening the political stranglehold of dominant parties. In fact, the adoption of such formal measures has given dominant parties a measure of international legitimacy, to varying degrees, while many of these nominally democratic regimes are restricting the expression of dissent, closing spaces for opposition, and clinging to power by constitutional amendments or popular referen